2020
DOI: 10.1101/2020.05.31.20118380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity and specificity of prediction models based on gustatory disorders in diagnosing COVID-19 patients: a case-control study

Abstract: Objective: to quantitatively assess disturbances of sweet, sour and salty and bitter tastes in a group of young, asymptomatic or oligosymptomatic COVID-19 patients; establish a reliable, sensitive and specific test that can diagnose COVID-19 on the basis of taste disorders and publish the results according to STARD 2015 statement (Standards for Reporting Diagnostic Accuracy). Design: case-control study Setting: isolated rooms in the Central Clinical Hospital of the Ministry of the Interior and Administration… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“… 32 , 33 , 34 While some studies have characterized the length and severity of smell and taste symptoms in COVID-19 patients, there is a growing recognition in the literature of the need for psychophysical gustatory testing in this population. 3 , 5 , 7 , 10 , 22 , 35 , 36 , 37 , 38 One goal of our study was to identify subjects with subclinical chemosensory dysfunction who do not have obvious symptoms of COVID-19. However, the low incidence of infection in our sample precluded us from such identification.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 34 While some studies have characterized the length and severity of smell and taste symptoms in COVID-19 patients, there is a growing recognition in the literature of the need for psychophysical gustatory testing in this population. 3 , 5 , 7 , 10 , 22 , 35 , 36 , 37 , 38 One goal of our study was to identify subjects with subclinical chemosensory dysfunction who do not have obvious symptoms of COVID-19. However, the low incidence of infection in our sample precluded us from such identification.…”
Section: Discussionmentioning
confidence: 99%
“…Gustatory function is exclusively assessed by subjective or self-reported impressions of COVID-19 patients on taste alteration, whereas a small number of objective studies were performed by applying primary tastants to the tongue [ 22 , 49 , 74 , 82 , 90 ]. Although taste sensitivity is reduced with increasing age and is higher in females than males, the objective test has been considered reliable to assess the tasting ability [ 141 ].…”
Section: Gustatory Dysfunctionmentioning
confidence: 99%
“…Abalo-Lojo et al [ 70 ] demonstrated that complete taste, bitter taste, salty taste, and sweet taste loss are present in 75.7%, 8.1%, 4.1%, and 1.4% of COVID-19 patients, respectively. Adamczyk et al [ 74 ] qualitatively assessed gustatory disorder by using solutions of sucrose (40–106.4 mg/mL), NaCl (13.5–27 mg/mL), ascorbic acid (6.25–12.5 mg/mL), and grapefruit extract (40 mg/mL). Sweet taste was especially impaired in COVID-19 patients, who could not recognize the lowest sucrose concentration.…”
Section: Gustatory Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Interestingly, RNA for SARS-CoV-2 was detected in the submandibular glands and tumor of a patient undergoing tongue surgery for squamous carcinoma two days before the patient developed symptoms and had a positive nasal swab for the virus: 3 however, taste tissue was not examined. The sensory symptoms need not be unitary as the virus can independently target all or any combination of the senses 4,5 and may even cause deficits or changes in a specific taste quality. Branches of five cranial nerves (CN I [smell], V [chemesthesis: heat, pungency], and VII, IX and X [taste, Figure 1A] are involved in relaying those specific senses to the central nervous system.…”
Section: Introductionmentioning
confidence: 99%